COMPETIÃ‡ÃƒO ENTRE VARIEDADES DE GERGELIM (ð˜šð˜¦ð˜´ð˜¢ð˜®ð˜¶ð˜® ð˜ªð˜¯ð˜¥ð˜ªð˜¤ð˜¶ð˜® L.) II. SEGUNDO ANO - Nakagawa, JoÃ£o; Toledo, Francisco Ferraz de; Machado, JosÃ© Ricardo (REVISTA DE AGRICULTURA, 2020)
COMPETIÃ‡ÃƒO ENTRE VARIEDADES DE GERGELIM (ð˜šð˜¦ð˜´ð˜¢ð˜®ð˜¶ð˜® ð˜ªð˜¯ð˜¥ð˜ªð˜¤ð˜¶ð˜® L.) II. SEGUNDO ANO